1988
DOI: 10.1161/01.cir.78.3.729
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response to prolonged reduction of myocardial blood flow distal to a severe coronary artery stenosis.

Abstract: Limited data are available concerning the effects of mild-to-moderate, sustained reductions of coronary blood flow on myocardial aerobic metabolism. This study tested the hypothesis that a sustained flow reduction distal to a severe coronary artery stenosis may be well tolerated (after the initial insult is passed) because of gradual improvement in the balance between myocardial oxygen supply and demand. Studies were performed in eight sedated, closed-chest domestic swine that were instrumented with an artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(40 citation statements)
references
References 19 publications
(2 reference statements)
1
36
0
2
Order By: Relevance
“…156,157,159 Myocardial creatine phosphate content decreases during the first few minutes of ischemia induced by partial occlusion but then returns toward normal within 60 to 85 minutes. 157,159 Fedele et al 160 showed that within 5 minutes after placement of a partial stenosis in an animal model of acute hibernation (in which necrosis did not occur), there was a significant reduction in anterior interventricular vein pH. However, by 180 minutes after stenosis placement, the pH had recovered to normal.…”
Section: The Concept Of Metabolic Adaptationmentioning
confidence: 99%
“…156,157,159 Myocardial creatine phosphate content decreases during the first few minutes of ischemia induced by partial occlusion but then returns toward normal within 60 to 85 minutes. 157,159 Fedele et al 160 showed that within 5 minutes after placement of a partial stenosis in an animal model of acute hibernation (in which necrosis did not occur), there was a significant reduction in anterior interventricular vein pH. However, by 180 minutes after stenosis placement, the pH had recovered to normal.…”
Section: The Concept Of Metabolic Adaptationmentioning
confidence: 99%
“…With this technique, hearts perfused aerobically with [1][2][3][4][5][6][7][8][9][10][11][12][13] C]glucose accumulate [3][4][5][6][7][8][9][10][11][12][13] C]alanine and [4][5][6][7][8][9][10][11][12][13] C]glutamate in proportion to rates of glycolysis and glucose-supported TCA cycle activity, respectively (18). Furthermore, the steady state [4][5][6][7][8][9][10][11][12][13] C] glutamate/ [3][4][5][6][7][8][9]…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, intracellular pools of glucose metabolites reach steady state 13 C enrichments which are lower than plasma glucose, and whose absolute value is determined by the relative contributions of plasma glucose, versus other precursor molecules, to the pool. Thus, the cytosolic pyruvate pool accumulates [3][4][5][6][7][8][9][10][11][12][13] C]pyruvate in proportion to the fraction of total glycolytic substrate supplied by exogenous 13 C-glucose, relative to other carbon sources (e.g.,…”
mentioning
confidence: 99%
“…Recent investigations of prolonged myocardial ischemia, a potential model of hibernating myocardium, have demonstrated initial depression and subsequent metabolic recovery by some measures despite persistently depressed myocardial blood flow and function.4,5 Specifically, lactate production has been noted to increase initially and then decrease during prolonged ischemia in the perfused heart6 and the intact pig. 4 Although it has been shown that phosphocreatine (PCr) concentrations return to normal during 1 hour of mild ischemia, 5 prolonged ischemia has been shown to reduce ATP levels in proportion to the degree of flow reduction. 5,7 Thus, the effect of prolonged ischemia on tissue phosphates has not been adequately defined, and it is unknown whether changes in high-energy phosphates are dissociated from, or parallel, changes in lactate metabolism.…”
mentioning
confidence: 99%